The Role of Security Personnel and Village Information Systems to Reduce Crime Rates in Rural Areas - Wida Reza Hardiyanti; Muhammad Khairil Anwar (Universitas Gadjah Mada, 2025)
Crime rates in rural areas have been increasing in recent years. This surge in criminal activity has fostered a climate of fear and insecurity among rural residents. Several factors contribute to this phenomenon. Many rural areas lack a sufficient number of security personnel, hindering effective deterrence and response to crime. Moreover, community members patrol (ronda), often struggles with ineffectiveness due to a lack of organization and resources. Furthermore, low awareness of basic security measures among rural residents leaves them vulnerable. Village information system also need to consider as one of the factors which might be influence the crime activities in villages. However, economic factors like poverty and unemployment can push individuals towards criminal activity. This study investigates the impact of increasing security personnel on crime rates and crime reporting in Indonesian villages using panel data from the PODES survey and SUSENAS from 2018-2022. The study employs a propensity score matching (PSM) model to examine the relationship between security personnel, crime rates, and crime reporting, considering other factors such as regulations, social assistance and socioeconomic factors. The study found that increasing security personnel has a significant negative impact on crime rates, indicating that a higher number of security personnel leads to a lower crime rate in villages. Additionally, enhancing village information system also has a significant positive impact on crime reporting which finally reduce crime. This research breaks new ground by comprehensively analyzing the interconnected nature of crime and its reporting within rural Indonesian communities. By demonstrating the effectiveness of increased security personnel and village information system will not only reducing crime rates but also encouraging reporting